Photon-plasmon coupling for fundamental-mode phase-matched third harmonic and triplet photon generation - Huang, Tianye (2020)
On-chip third harmonic generation (THG) and its inverse process, namely, the generation of entangled triplet photons with Greenberger-Horne-Zeilinger state, have attracted much interest in the last decade. To enhance the conversion efficiency or photon creation rate in optical waveguides, phase matching is a crucial condition, which must be satisfied. However, material dispersion usually prevents the phase matching condition between input pump and generated radiation when they are both guided in the fundamental modes. In this paper, a dielectric-loaded waveguide based on fundamental mode photon-plasmon coupling is proposed for efficient THG and triplet photon generation (TPG). Leveraging on the unique dispersion properties of transparent conductive oxide, the third harmonic radiation can be guided by the conventional photonic mode in the near-infrared, while the pump frequency is confined by a surface plasmon polariton mode in the mid-infrared. According to our simulations, the THG efficiency and TPG rate can achieve ∼10-4 and 32 Hz, respectively. The proposed waveguide can be a promising platform for all-optical and quantum signal processing.